Alexis St. Martin Gastropexy: A Novel Technique for Gastropexy During Percutaneous Endoscopic Gastrostomy Tube Placement. Issue 2 (April 2019) - Halka, Joshua T.; Yee, Danielle; Angus, Andrew; Mohammed, Azmath; Sevak, Shruti; Robbins, James
Abstract : Background: Percutaneous endoscopic gastrostomy (PEG) is a preferred method of long-term enteral nutritional support. Despite its ease of placement, it has a 4% major complication rate, requiring surgical intervention or hospitalization. Early PEG tube dislodgment can cause peritonitis, requiring emergent laparotomy at significant morbidity and cost. T-fasteners have been used as an adjunct gastropexy, but nearly one third migrate into the abdominal wall within the first 2 weeks. We describe a low-cost, minimally invasive technique using widely available surgical instruments to appose the gastric and abdominal walls. Methods: All PEG procedures were performed in our 60-bed surgical intensive care unit. Institutional IRB approval was obtained along with procedure specific consent for all patients. The adjunctive gastropexy procedure was performed on four patients at high risk for early PEG tube dislodgment. Following routine PEG tube placement, both ends of four 2-0 polyglactin ties were brought through the gastric and abdominal walls through separate stab incisions adjacent to the PEG tube exit site in the 3, 6, 9, and 12 o'clock positions. These were tied in the subcutaneous tissue, securing the gastric wall to the abdominal wall. Results: No PEG tube complications occurred. All patients were discharged to long-term care facilities with PEG tubes intact or electively removed. Conclusions: We describe the results of a pilot study for a cost-effective, easily implementable, adjunct technique, named after the namesake of our institution, to decrease the incidence and severity of complications associated with PEG tube dislodgment. It was used in 4 patients at high risk for PEG tube dislodgment with satisfactory early results in all 4. Further recruitment of larger numbers of patients using this technique is ongoing to determine if this technique is truly effective at reducing PEG tube complications.